Low-Energy Electron-Induced Dissociation of the Radiosensitizing Agent Sanazole - Izadi, Farhad; Mahmoodi-Darian, Masoomeh; Luxford, Thomas F M; Kočišek, Jaroslav; Denifl, Stephan; Ončák, Milan (ChemPlusChem, 2025)
Sanazole is a hypoxic radiosensitizer for which the activation mechanism in cells has been suggested to involve initial reduction. Herein, electron attachment to sanazole under isolated conditions and upon microhydrations is investigated. Employing mass spectrometry supported by quantum chemical calculations, the anion formation mechanism and subsequent fragmentation pathways are examined. In the case of electron attachment to the isolated molecule, predominantly dissociative electron attachment is observed. The most prominent fragment anion, (NTR-yl)- at m/z 113, is suggested to be formed in an exothermic pathway through a single-bond dissociation, whereas other intense fragments require structural reorganization. The limited abundance of the parent anion under isolated conditions is altered upon microhydration conditions since in the latter situation only the (microhydrated) parent anion is observed. This result suggests that hydration closes and/or slows down the dissociation process and indicates that for sanazole, the initial mechanism of action in a reductive cell environment may be similar to that of well-studied nitroimidazole radiosensitizers.
Keywords: Triazoles; Electrons; radiosensitizer; hmotnostní spektrometrie; elektrony; Radiation-Sensitizing Agents; sanazol; Mass Spectrometry; electron attachment; triazoly; radiosenzibilizující látky; electron‐induced dissociation